A Phylogenomic and Molecular Markers Based Analysis of the Class Acidimicrobiia - Hu, Danyu; Cha, Guihong; Gao, Beile (Frontiers in Microbiology, 2018)
Recent metagenomic surveys of microbial community suggested that species associated with the class Acidimicrobiia are abundant in diverse aquatic environments such as acidic mine water, waste water sludge, freshwater, or marine habitats, but very few species have been cultivated and characterized for this class. The current taxonomic framework of Acidimicrobiia is solely based on 16S rRNA sequence analysis of few cultivable representatives, and no molecular, biochemical or physiological characteristics are known that can distinguish species of this class from the other bacteria. This study reports the most comprehensive phylogenomic analysis for 20 sequenced members of this class and revealed 3 additional major lineages in addition to the two recognized families. In parallel, comparative analysis of the sequenced Acidimicrobiia species identified 15 conserved signature indels (CSIs) in widely distributed proteins and 26 conserved signature proteins (CSPs), which are either specific for this class as a whole or to its major lineages. This study represents the first comprehensive phylogenetic analysis of the class Acidimicrobiia and the identified CSIs and CSPs provide useful molecular markers for the identification and delineation of species belonging to this class or its subgroups.